Algorithmic characterization of pentadiagonal ASSR matrices. Issue 1 (1st February 2020) - Alonso, P.; Peña, J. M.; Serrano, M. L.
ABSTRACT: A matrix is sign regular if all its minors of the same order are of the same sign. A very important subclass of sign regular matrices is formed by those matrices whose non-trivial minors are non-zero. These matrices are called almost strictly sign regular matrices. In this work, an algorithmic characterization of pentadiagonal almost strictly sign regular matrices is presented.